Yuzu and hesperidin ameliorate blood-brain barrier disruption during hypoxia via antioxidant activity - Lee, Bo Kyung; Hyun, Soo Wang; Jung, Yi Sook (Antioxidants, 2020)
Yuzu and its main component, hesperidin (HSP), have several health benefits owing to their anti-inflammatory and antioxidant properties. We examined the effects of yuzu and hSP on blood–brain barrier (BBB) dysfunction during ischemia/hypoxia in an in vivo animal model and an in vitro BBB endothelial cell model, and also investigated the underlying mechanisms. In an in vitro BBB endothelial cell model, BBB permeability was determined by measurement of Evans blue extravasation in vivo and in vitro. The expression of tight junction proteins, such as claudin-5 and zonula occludens-1 (ZO-1), was detected by immunochemistry and western blotting, and the reactive oxygen species (ROS) level was measured by 2′7′-dichlorofluorescein diacetate intensity. Yuzu and hSP significantly ameliorated the increase in BBB permeability and the disruption of claudin-5 and ZO-1 in both in vivo and in vitro models. In bEnd.3 cells, yuzu and hSP were shown to inhibit the disruption of claudin-5 and ZO-1 during hypoxia, and the protective effects of yuzu and hSP on claudin-5 degradation seemed to be mediated by Forkhead box O 3a (FoxO3a) and matrix metalloproteinase (MMP)-3/9. In addition, well-known antioxidants, trolox and N-acetyl cysteine, significantly attenuated the BBB permeability increase, disruption of claudin-5 and ZO-1, and FoxO3a activation during hypoxia, suggesting that ROS are important mediators of BBB dysfunction during hypoxia. Collectively, these results indicate that yuzu and hSP protect the BBB against dysfunction via maintaining integrity of claudin-5 and ZO-1, and these effects of yuzu and hSP appear to be a facet of their antioxidant properties. Our findings may contribute to therapeutic strategies for BBB-associated neurodegenerative diseases.
Keywords: Blood–brain barrier (BBB); Hesperidin (HSP); Hypoxia; Reactive oxygen species (ROS); Tight junction (TJ); Yuzu